Area-based Health Workforce Planning: Health Workforce Supply Projection of the Public Health Inspection, Zone 3, Ministry of Public Health - Patanavanichanan, Nattaya; Pagaiya, Nonglak (Journal of Health Science of Thailand, 2017)
The study was aimed at accessing health workforce database in relation to distribution and health workforce supply projection in the next 5 years in order to prepare inputs for health workforce planning of the public health inspection, zone 3, Ministry of Public Health. Checklist for data collection comprising: health workforce distribution, health workforce gain and loss over the past 3 years; was prepared by researchers. Data was analyzed in percentage and forecast health workforce supply for the next 5 years. The results show that high mobility was found among general doctors, although gain rate was higher than loss rate, particularly at community hospitals. The problems laid on the specialists, particularly obstetricians and general surgeons where the loss rate was higher than the gain rate. Registered nurses, as well, turnover was as high as gain rate. It was even worse, at regional and general hospitals, where turnover of registered nurses was higher than new comers. Health workforce situation at primary health care facilities was much better during the past 3 years. However, the situation of temporary employment of about 20 percent of health workforce was risk resignation. The 5 year supply projection showed that obstetricians, general surgeons and registered nurses would be in great demand due to shortages. This suggests that to manage health workforce to be equitably distributed, measures need to address both to reduce loss rate and increase new workforce to the labor market.